SUPPLY CHAIN NETWORK MODEL OF TRADITIONAL MARKET FOR WHITE SUGAR COMMODITIES (CASE STUDY: WEST JAVA) - (NIM : 23411049); Pembimbing : Suprayogi, Ph.D ; Dr. Yosi Agustina Hidayat, SUTANDI
The traditional market is a trading entity that supports the Indonesian economy with the employment of 12.5 million workers, spreaded over 13.450 merchants traditional market unit. On the development of traditional market has threaten out by the existence of the modern market. The share trades of traditional market decreased 2% per year, from 75% in 2002 to 59% in 2010 (AC Nielsen, 2011). The long supply chain system and transfer of ownership are some problem on traditional market. Howeve, the existing policies unable to notice it. Transfer of ownership will cause an increase in distribution costs. This impacts on inefficient distribution channels and increasing selling price of goods at the end of the level. White sugar is one of the basic needs commodities, which the price influenced directly by inflation rate. The impact of supply shortages and inefficient distribution network will create price volatility of white sugar in the domestic regional. The purpose of this study is to develop a supply chain network model of traditional markets for white sugar commoditi with a case study of West Java. The developed model is adapted from the the characteristics of the distribution system of white sugar in the traditional market. The performance criteria to minimizing logistics total cost. Benchmark models of this study are the model of Saragi (2005) and the model of Hidayanti (2008) concerning the determination of location of the warehouse distribution facility. Model solution using Integer Linear Programming (ILP) with the help of Lingo software version 9.0. From the results of the proposed model it is found that the total logistics cost is Rp.160.403.940.760,- per year. With the decision to open 9 (nine) distributor, 3 (three) sub-distributor and 7 (seven) wholesaler. The proposed model successful to reduces 31% cost from the existing condition of traditional market distribution network after increase 11% of warehouse capacity. Meanwhile, when compared with a distribution network of modern market which has total logistics cost of Rp 160.804.298.500,- per year, the total logistics of costs proposed model is lower.